2020
DOI: 10.1111/jocd.13731
|View full text |Cite
|
Sign up to set email alerts
|

The use of botulinum toxin A in upper lip augmentation

Abstract: A plump lip is the symbol of youth and glamorousness. Influenced by sun damage, genetic factors, and smoking, aging will cause volume loss and perioral wrinkles to the lip. 1 Lip augmentation with dermal filler is frequently performed to offset the age-related changes and provides a more attractive appearance. 2 Botulinum toxin A (BTA) is a naturally occurring polypeptide chain molecule derived from the Clostridium botulinum bacterium. By blocking the release of acetylcholine at the myoneural junction, BTA inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 9 publications
(15 reference statements)
0
13
0
1
Order By: Relevance
“…In total, 780 patients were enrolled in the nine studies. [ 8 , 12 , 29 , 33 , 45 49 ] In eight studies that reported descriptive gender data, 91.07% of the patients were women( n =683), 7.33% were men( n= 55) and 1.60% were transgender( n =12). [ 8 , 12 , 29 , 45 49 ] The mean age at treatment was 46.01 years with a range of 21 to 83 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 780 patients were enrolled in the nine studies. [ 8 , 12 , 29 , 33 , 45 49 ] In eight studies that reported descriptive gender data, 91.07% of the patients were women( n =683), 7.33% were men( n= 55) and 1.60% were transgender( n =12). [ 8 , 12 , 29 , 45 49 ] The mean age at treatment was 46.01 years with a range of 21 to 83 years.…”
Section: Resultsmentioning
confidence: 99%
“…[ 8 , 12 , 29 , 33 , 45 49 ] In eight studies that reported descriptive gender data, 91.07% of the patients were women( n =683), 7.33% were men( n= 55) and 1.60% were transgender( n =12). [ 8 , 12 , 29 , 45 49 ] The mean age at treatment was 46.01 years with a range of 21 to 83 years. The mean time to follow-up was 31.48 months with a range from 2 months to 10 years.…”
Section: Resultsmentioning
confidence: 99%
“…A atuação da boca como protagonista na atratividade facial se deve a predominância de tamanho e mobilidade em relação a outras estruturas do complexo facial e estomatognático. A boca concentra expressões sensitivas, afetivas e instintivas das atividades ao longo da vida, além de atuar como órgão receptor, permitindo ingestão de alimentos e degustação, permeando trocas com o ambiente através da exteriorização de sons, palavras e expressões mímicas 8 .…”
Section: Discussionunclassified
“…There is no effective correction for the complete muscle block but waiting until the toxin action wanes; touch-up sessions may help in case of asymmetries. 31 Botulinum Toxin and the Facial Lower Third DAO: marionette lines are mainly caused by the ptosis of soft cheek tissues. The DAO muscle is causally important when the muscle tone is excessive because this muscle depresses the oral commissures-the typically sad facial expression is the outcome.…”
Section: The Occasional Shortcomings Of Botulinum Toxin and Their Managementmentioning
confidence: 99%
“…There is no effective correction for the complete muscle block but waiting until the toxin action wanes; touch-up sessions may help in case of asymmetries. 31…”
Section: Botulinum Toxin and The Facial Middle Thirdmentioning
confidence: 99%